2011
DOI: 10.1177/070674371105601102
|View full text |Cite
|
Sign up to set email alerts
|

Extending Motivational Interviewing to the Treatment of Major Mental Health Problems: Current Directions and Evidence

Abstract: Motivational interviewing (MI) was originally developed for the treatment of substance abuse but is rapidly expanding to other major mental health populations beyond addictions. This brief review considers the use of MI and related motivational enhancement therapies (METs) in the treatment of anxiety, depression, and eating disorders, and concurrent psychosis and substance use disorders. MI-MET has been added and (or) integrated into treatment for these problems in a wide variety of ways, most commonly as a pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(46 citation statements)
references
References 67 publications
0
43
0
3
Order By: Relevance
“…An electronic database search of PsycINFO, Embase, Web of Science, Sage, Scopus, ProQuest Dissertations and Theses, and Google Scholar was conducted using the following keywords: motivational interviewing, motivational enhancement therapy, brief intervention, mechanisms of action, mediator, moderator, and therapy process. Hand-searches of the online MI bibliography posted on the MI website (http://www.motivationalinterview.org) were also conducted, as well as hand-searches of relevant commentaries, review, and meta-analytic papers (Apodaca & Longabaugh, 2009;Burke, 2011;Flynn, 2011;Geller & Dunn, 2011;Simpson & Zuckoff, 2011;Westra et al, 2011). Database searches were conducted up until March 2013.…”
Section: Inclusion Criteriamentioning
confidence: 99%
See 1 more Smart Citation
“…An electronic database search of PsycINFO, Embase, Web of Science, Sage, Scopus, ProQuest Dissertations and Theses, and Google Scholar was conducted using the following keywords: motivational interviewing, motivational enhancement therapy, brief intervention, mechanisms of action, mediator, moderator, and therapy process. Hand-searches of the online MI bibliography posted on the MI website (http://www.motivationalinterview.org) were also conducted, as well as hand-searches of relevant commentaries, review, and meta-analytic papers (Apodaca & Longabaugh, 2009;Burke, 2011;Flynn, 2011;Geller & Dunn, 2011;Simpson & Zuckoff, 2011;Westra et al, 2011). Database searches were conducted up until March 2013.…”
Section: Inclusion Criteriamentioning
confidence: 99%
“…However, in the treatment of psychological disorders such as anxiety and eating disorders, MI is primarily used as an adjunctive treatment with an aim to enhance treatment gains as a result of another treatment. In these areas, employing MI is thought to facilitate patient motivation and engagement in other treatment (e.g., cognitive behavioural treatment; CBT), thereby potentially yielding more positive outcomes (Westra, Aviram, & Doell, 2011). Given that the focus of MI may differ across populations it is possible that the mechanisms of change in MI for substance use disorders may not apply when MI is used for other disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Motivational Interviewing is an established practice model, with mounting evidence in research for its effective improvement of psychosocial risks, especially mental health (Brody, 2009;Westra, 2004;Zerler, 2009), substance abuse (Gingerich & Peterson, 2013;Johnson, Sacks, & Edmonds, 2010;Simpson & Zuckoff, 2011;Westra, Aviram, & Odell, 2011), alcohol abuse (Branscum & Sharma, 2010;Feldstein & Forcehimes, 2007;Harris, Aldea, & Kirkley, 2006;Martens, Smith, & Murphy, 2013), and eating disorders (Knowles, Anokhina, & Serpell, 2013;Macdonald, Hibbs, Corfield, & Treasure, 2012;Weiss, Mills, Westra, & Carter, 2013). Gingerich and Peterson (2013) found that MI is also cost-effective, requires fewer therapeutic sessions, and is adaptable to a variety of environments more so than other intervention solutions.…”
Section: Motivational Interviewing (Mi)mentioning
confidence: 99%
“…Given that effective use of MI with dually diagnosed individuals likely requires an especially high level of therapeutic skill (Martino & Moyers, 2008), it is essential that future research remedy this omission. Second, when MI is combined with CBT, it is unclear whether the integration is being implemented in a manner that preserves MI's efficacy for increasing motivation to change (Westra et al, 2011). For instance, relying on a protocol that calls for the initiation of CBT after one or two introductory sessions of MI, regardless of the individual's response to MI, risks a premature focus on how to change when some patients are still deciding whether to change (Moyers & Houck, 2011).…”
Section: Summary and Critique Of MI And Cbt Studiesmentioning
confidence: 99%
“…The most frequently studied of these behavioral interventions have been motivational interviewing (MI; W.R. Miller & Rollnick, 2013), cognitive-behavioral therapy (CBT; Marlatt & Gordon, 1985), contingency management (CM; Higgins, Silverman, & Heil, 2008) and combinations of these interventions (e.g., MI + CBT). Motivational interventions with SMI individuals focus on engaging patients in a dialogue that is intended to increase their motivation and commitment to changing substance use (Martino, 2007; Westra, Aviram, & Doell, 2011). Cognitive-behavioral treatments emphasize teaching of skills to overcome deficits in interpersonal and intrapersonal life areas that are seen as functionally related to substance abuse, thus improving individuals’ ability to cope with high-risk situations and relapse precipitants (e.g., Kadden et al, 1994).…”
Section: Introductionmentioning
confidence: 99%